PENGATURAN FUNGSI PENGAWASAN INTERNAL TERHADAP HAKIM KONSTITUSI SEBAGAI UPAYA MEWUJUDKAN KEKUASAAN KEHAKIMAN YANG MERDEKA (STUDI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 1-2/PUU-XII/2014) - Sarif, Himawan Achmad; Firdaus, Sunny Ummul (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
This writing aims to analyze the regulation of internal supervisory functions of Constitutional Justices as an effort to realize independent judicial power and to analyze the implications of Constitutional Court Decision Number 1-2 / PUU-XII / 2014 on the implementation of supervision of Constitutional Justices.This type of research is normative legal research that is prescriptive which is using a statutory approach, case approach, historical approach and conceptual approach. Sourceof legal materials of this research were obtained from primary legal materials and secondary legal materials that relating to legal issues reviewed. Primary legal materials used in the form of legislation and judgment decisions, while the secondary legal materials used in the form of publications about the law that is not an official document. Techniques of collecting legal materials used are document studies or literature studies which are then analyzed using the deduction method.Based on the result of the research, it is concluded that the supervision of Constitutional Justice is initially in the form of internal and external supervision which arrangement based on Law Number 24 Year 2003 and Article 24B of the 1945 Constitution of the Republic of Indonesia Year 1945 which is further regulated in Law Number 22 Year 2004. The arrangement is changed due to the Decision The Constitutional Court Number 005/PUU-IV/2006 which makes internal controls the only supervisory system of Constitutional Justices, thereafter the supervision of the Constitutional Justices underwent several dynamics of change in order to establish effective oversight. In 2013 the Court experienced a tremendous crisis that resulted in the loss of public confidence. In response to that the government enacted Perpu No. 1 of 2013 which was then ratified into Law No. 4 of 2014. However, the law was revoked by the Constitutional based on the Constitutional Court’s Decision Number 1-2/PUU-XII/2014. The implication of the decision is the re-enactment of Law Number 8 Year 2011 and the supervision of Constitutional Court Justice is further stipulated in PMK Number Year 2014.